Quando o olhar é capturado: o fascínio dos adolescentes pela filmografia de horror - Cantarelli, Natalia Dalla Côrte (2015)
The present study sought to understand the interest teenagers have of the horror genre. In order to achieve this objective, the research is qualitative approach, features an exploratory character, and utilizes a focal group as a data analysis technique. The focal group was comprised of students from a state school in the countryside of the state of Rio Grande do Sul. The school has a project that aims to develop a cinema workshop in which the focal group had been attending in order to produce a short film of their liking. In order to select participants, the students who had attended the cinema workshop were informed about the objectives and asked if they would like to participate. Sixteen teenagers showed interest and were divided into three focal groups. Respectively, the groups were composed of 5, 3 and 8 participants. The number of participants in each group was based on the saturation criteria, which limits the number of people in a group when the participants no longer come up with new ideas in terms of content as they because repetitive. Regarding the data analysis, a content analysis technique was utilized. The categories were based upon the analysis and were presented in two articles, in a way that the categories converge in order to comprehend the great interest that teenagers display regarding the horror genre. The first article approaches such matter in a wide manner and analyses the participants speech as to grasp the intimate relation between adolescence and horror films. The article also presents and discusses the first moments and the importance of these encounters with cinema, as well as the meaning to the participants. The second article focuses on the horror genres relevance and singularities towards the participants. The results point to the fact that the fascination unleashed by these films occupies a privileged place in the teenagers lives. Being in front of these moving images, as well as in a dream, allows the participants to live within a mirror maze, allowing them to meet with what is the realest, the most private and most obscure of themselves. Furthermore, the contact with film narratives when practiced in childhood is related to the absence of parents, the experience of abandonment lived by others. Contact with fiction allows them to actively experience horror, which in real life, was experienced passively and traumatically. The presence of the horror genre returns intensively in adolescence due to great changes during puberty and excessive impulses. Hence, teenagers have the need to witness this being experienced by others to be able get through this phase in their lives. However, again, teenagers see themselves as abandoned and seek, in the horror genre, the possibility of an active position, in addition to shared experiences, which constructs a symbolic bond.